ANALISIS IMPLEMENTASI PERATURAN DAERAH NOMOR 9 TAHUN 2014 TENTANG DESA (Studi Kasus Di Desa Jayanti Kecamatan Jayanti Kabupaten Tangerang) - Ramadhan, Usia; Hartoko, Gatot; Alwajir, Dede Qodrat (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study was designed to analyze the implementation of Local Regulation No. 9 of 2014 concerning Villages in the Tangerang Regency, with a case study of Jayanti Village. The main focus was on road infrastructure that had suffered severe damage but had not yet received adequate repairs. This phenomenon is an important issue considering that village roads play a vital role as the main supporting facility for the social and economic activities of the local community. Although the planning process has been carried out through mechanisms such as hamlet meetings (musdus), village meetings (musdes), and development planning meetings (musrenbang), the community's aspirations regarding road infrastructure improvements have not been fully realized. The method used is a descriptive qualitative approach. Data collection was carried out through in-depth interviews with village officials, community leaders, and villagers, as well as documentation and direct observation in the field. Data analysis focused on three main variables in policy implementation as proposed by George C. Edward III, namely communication, resources, and disposition, as well as the bureaucratic structure at the village level. This study shows that the implementation of Local Regulation No. 9 of 2014 in Jayanti Village has not reached an optimal level, especially in the context of sustainable road infrastructure development. The discrepancy between the plans developed at the village level and their technical implementation in the field reflects weaknesses in effective supervision and coordination between village governments and relevant agencies. The results of the study show that there are significant obstacles in terms of inter-agency coordination, budget constraints, and inadequate implementation capacity to follow up on the agreed planning results. Therefore, efforts are needed to improve the capacity of village officials, enhance inter-agency cooperation, and improve information to the community so that the development process can be more responsive to the needs of residents.